Education On Hormonal Changes During Perimenopause and Menopause in Japan in 2025 - Rukmaini; Enok Siti Roiyatul Mahmudah; Rodiawati; Rena Herlina; Sri Suparti; Surani; Al Silva Nur Aniza; Sri Komala Dewi (Rajaki of Tulip Medika Publisher, 2025)
The Background: Hormonal changes that occur in women during perimenopause and menopause can have various impacts on physical and psychological health. A lack of understanding of these changes can lead to unpreparedness in dealing with the symptoms that arise. Therefore, this community service activity aims to provide education to premenopausal and menopausal women to better understand the hormonal changes that occur and strategies for managing them. The method used in this activity was direct counseling through seminars and interactive discussions. The material presented covered hormonal changes, their impact on health, and steps that can be taken to address the symptoms that arise. Evaluation was conducted using questionnaires before and after the activity to measure participants' understanding. The results of the activity showed a significant increase in participants' knowledge of the hormonal changes that occur during perimenopause and menopause. Participants were also better prepared to deal with the symptoms that arise and understood the importance of maintaining a healthy lifestyle. In conclusion, education about hormonal changes in premenopause and menopause is crucial for increasing women's awareness and preparedness in facing this phase. Similar activities need to be continued to have a broader impact on improving the well-being of older women.